Cellular and molecular mechanisms of muscle atrophy - Paolo Bonaldo; Marco Sandri (The Company of Biologists, 2013)
Skeletal muscle is a plastic organ that is maintained by multiple pathways regulating cell and protein turnover. During muscle atrophy, proteolytic systems are activated, and contractile proteins and organelles are removed, resulting in the shrinkage of muscle fibers. Excessive loss of muscle mass is associated with poor prognosis in several diseases, including myopathies and muscular dystrophies, as well as in systemic disorders such as cancer, diabetes, sepsis and heart failure. Muscle loss also occurs during aging. In this paper, we review the key mechanisms that regulate the turnover of contractile proteins and organelles in muscle tissue, and discuss how impairments in these mechanisms can contribute to muscle atrophy. We also discuss how protein synthesis and degradation are coordinately regulated by signaling pathways that are influenced by mechanical stress, physical activity, and the availability of nutrients and growth factors. Understanding how these pathways regulate muscle mass will provide new therapeutic targets for the prevention and treatment of muscle atrophy in metabolic and neuromuscular diseases.